Toward Sustainable Bauxite Chains: Comparing Indonesia and Global Practices to Advance SDG 9 - Rohmatika, Fiya Ainur; Paksi, Arie Kusuma (Universitas prof. Dr. Moestopo (Beragama), 2026)
This study analyzes Indonesia’s bauxite downstreaming strategy within the framework of United Nations Sustainable Development Goal 9 (SDG 9) and compares it with international experiences in Australia and Guinea. The research employs a qualitative design using case study and comparative policy analysis methods based on secondary data from government reports, statistical agencies, international organizations, and academic literature. The analysis is structured around three key SDG 9 dimensions: industrial capacity (target 9.2), process sustainability (target 9.4), and technological innovation (target 9.5). The findings show that Indonesia’s alumina refining capacity increased from 1.4 million tons in 2021 to approximately 5.3 million tons in 2024, while value added rose from about US40 per ton of bauxite ore to around US400 per ton of alumina. Despite this progress, structural challenges remain, including dependence on imported aluminum to meet 54% of domestic demand, a workforce dominated by contractual workers with limited skills transfer, foreign capital controlling 56–63% of downstream projects, and red mud waste generation estimated at 6.36–7.95 million tons annually with minimal utilization. The study concludes that sustainable downstreaming requires comprehensive policies beyond export restrictions, including infrastructure strengthening, low-carbon energy transition, technology transfer, increased R&D investment, ESG adoption, and diversified international partnerships.